Determinants of Halal Fashion Purchase Behavior: Integrating Religiosity with the Theory of Interpersonal Behavior - Rahmawaty, Anita; Kusrini, Eni; Restuti, Dwi Putri (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2026)
This study examines the determinants of Muslim consumer behavior in buying halal fashion by integrating religiosity with the TIB (Theory of Interpersonal Behavior) model. There are eight variables in this study: religiosity, attitude, affect, social factor, habit, facilitating condition, purchase intention, and purchase behavior. This quantitative study uses data from 216 Muslim consumers in Central Java and analyzes them using PLS-SEM. The findings of this study show that religiosity can have a greater increase effect on attitudes, affect, social factors, and habits. Affect, habit, and facilitating conditions positively affects halal fashion purchase intention, but religiosity, attitude, and social factors do not have a direct effect on purchase intention. Meanwhile, habits, facilitating conditions, and purchase intention have a significant direct effect on halal fashion purchase behavior. The results of this study are expected to benefit Islamic businesspeople by helping them understand the factors that shape Muslim consumers’ behavior when purchasing halal fashion products.